2015
DOI: 10.1162/jocn_a_00816
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate fMRI and Eye Tracking Reveal Differential Effects of Visual Interference on Recognition Memory Judgments for Objects and Scenes

Abstract: Recent work has demonstrated that the perirhinal cortex (PRC) supports conjunctive object representations that aid object recognition memory following visual object interference. It is unclear, however, how these representations interact with other brain regions implicated in mnemonic retrieval and how congruent and incongruent interference influences the processing of targets and foils during object recognition. To address this, multivariate partial least squares was applied to fMRI data acquired during an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 73 publications
(96 reference statements)
3
10
0
Order By: Relevance
“…Consistent with past research in younger adults (Watson and Lee, 2013;O'Neil et al, 2015), we found that across all participants, object interference had a detrimental impact on object recognition relative to scene recognition (Fig. 3B).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with past research in younger adults (Watson and Lee, 2013;O'Neil et al, 2015), we found that across all participants, object interference had a detrimental impact on object recognition relative to scene recognition (Fig. 3B).…”
Section: Discussionsupporting
confidence: 90%
“…This task was adapted from previous studies (Watson and Lee, ; O'Neil et al, b) and with these adaptations, we found that object and scene recognition were no longer equated in difficulty, and that object recognition resulted in higher performance than scene recognition in a group of young adults. That is, we found that condition most closely associated with cognitive status was actually easier.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The DLPFC has been shown to be involved in memory retrieval (Dudukovic & Kuhl, ), and in particular it has been implicated in retrieval success, as demonstrated in a large meta‐analysis by Spaniol and colleagues (Spaniol et al, ). In a recent study, O'Neil, Watson, Dhillon, Lobaugh, and Lee () showed that the DLPFC, perirhinal cortex, and posterior parietal lobe are preferentially recruited under conditions of high visual interference, similar to the mnemonic similarity task used in the present study. Our results extend this finding by showing that the DLPFC is even more critical following a 12‐hr waking delay as compared to a delay that contains sleep.…”
Section: Discussionsupporting
confidence: 55%
“…The added information that neuroimaging and potentially other biomarkers may provide in interpreting SVT/PVT findings, should be the focus of large studies with varied populations of individuals, disorders and neuroimaging findings. Furthermore, the burgeoning fields of functional neuroimaging and electrophysiological techniques including eyetracking that examine the genuineness of cognitive performance has important implications for validity determination (Astafiev et al 2015;Matthews et al 2015;O'Neil et al 2015;van Hooft and Born 2012). This literature was only touched upon and not systematically reviewed.…”
Section: Considerations -What Neuroimaging and Cognitive Neurosciencementioning
confidence: 99%